Macroeconomic shocks and volatility spillovers between stock, bond, gold and crude oil markets - Yongdeng Xu; Bo Guan; Wenna Lu; Saeed M. Heravi (Cardiff University, Cardiff Business School, 2024)
This paper introduces a novel model to analyse the impact of macroeconomic shocks on volatility spillovers within key financial markets, such as Stock, Bond, Gold and Crude Oil. By treating macroeconomic variables as external factors to financial market volatility, our study distinguishes between internal financial volatility spillovers and external shocks arising from macroeconomic changes. Our analysis reveals that without macroeconomic shocks, the Stock market predominantly acts as the main source of volatility spillovers, with Crude Oil being the principal spillover recipient. However, the Stock market's role in driving volatility spillover, especially towards the Crude Oil market, changes markedly in the context of macroeconomic shocks. These shocks exert a more substantial impact on Crude Oil compared to other markets. In contrast, the Bond and Gold markets exhibit a lower level of volatility transmission and are less influenced by macroeconomic shocks, thereby reinforcing their roles as stabilizers within the financial system.
Keywords: C32; C52; G14; 330; Volatility spillover; Macroeconomic shocks; Multiplicative Error Model; Realizedvolatility; Financial markets